Modeling the Competitive Effect of Euphorbia dracunculoides and Astragalus sp. in Zero Input Rainfed Chickpea - IKRAM,R.M. (2018)
ABSTRACT: Brown chickpea (Cicer arietinum L.) is one of the two chickpea types grown in Pakistan and other countries. The critical period for weed removal in a rainfed chickpea system is an important consideration in devising weed management strategies. Field experiments were conducted in the winter season of 2011 and 2012 to determine the extent of yield loss with different periods of weed crop competition. Seven weed crop competition periods (0, 45, 60, 75, 90, 105 and 160 days after sowing - DAS) were used to identify the critical period for weed removal in rainfed chickpea. Experimental plots were naturally infested with Euphorbia dracunculoides and Astragalus sp. in both years. Individual, composite density and dry weights of E. dracunculoides and Astragalussp. increased significantly with an increase in the competition period. However, yield and yield-contributing traits of chickpea significantly decreased with an increase in the competition period. Chickpea seed yield loss was 11-53% in different weed crop competition periods. Euphorbia dracunculoides and Astragalus sp. removed 39.9 and 36.9 kg ha-1 of N, 9.61 and 7.27 kg ha-1 of P and 38.3 and 36.9 kg ha-1 of K, respectively. Season long weed competition (160 days after sowing) resulted in 19.5% seed protein content compared with 24.5% seed protein content in weed-free chickpea. A Logistic equation was fitted to yield data in response to increasing periods of weed crop competition. The critical timing of weed removal at 5 and 10% acceptable yield losses were 26 and 39 DAS, respectively. The observed critical period suggests that in rainfed chickpea, a carefully timed weed removal could prevent grain yield losses.